1988
DOI: 10.1056/nejm198805123181904
|View full text |Cite
|
Sign up to set email alerts
|

Protection by Milk Immunoglobulin Concentrate against Oral Challenge with EnterotoxigenicEscherichia coli

Abstract: Enterotoxigenic Escherichia coli is a common cause of traveler's diarrhea. Prophylaxis against traveler's diarrhea has been associated with side effects from bismuth subsalicylate and the development of resistance to antimicrobial agents. We undertook a double-blind controlled trial in which a bovine milk immunoglobulin concentrate with high titers of antibodies against enterotoxigenic E. coli was used as prophylaxis against E. coli challenge in volunteers. Lyophilized milk immunoglobulins were prepared from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
157
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(165 citation statements)
references
References 32 publications
6
157
2
Order By: Relevance
“…There are different serotypes of ETEC strains producing a variety of CFs (Wolf, 1997). ETEC strain H10407 (O78 : H11 : CFA/I : LT + : STIb + ), a clinical isolate from a patient in Bangladesh (Evans & Evans, 1973), is a prototypic virulent strain, which has been tested in oral challenge studies and shown to cause diarrhoea in humans (Tacket et al, 1988)). Like most ETEC, strain H10407 carries plasmids and these encode most of the virulence determinants described so far such as CFs, LT and ST (Evans et al, 1975;Smith et al, 1979;Yamamoto & Yokota, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…There are different serotypes of ETEC strains producing a variety of CFs (Wolf, 1997). ETEC strain H10407 (O78 : H11 : CFA/I : LT + : STIb + ), a clinical isolate from a patient in Bangladesh (Evans & Evans, 1973), is a prototypic virulent strain, which has been tested in oral challenge studies and shown to cause diarrhoea in humans (Tacket et al, 1988)). Like most ETEC, strain H10407 carries plasmids and these encode most of the virulence determinants described so far such as CFs, LT and ST (Evans et al, 1975;Smith et al, 1979;Yamamoto & Yokota, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The second generation was colostrum from cows immunized with various food-borne pathogens or its immunoglobulin concentrate. Clinical trials revealed that immune cow colostrum effectively prevents infection with enterotoxigenic E. coli (O78:H11), rotavirus (2,12), and Cryptosporidium parvum (17). The third generation is colostrum derived from healthy non-immunized pasture fed cows.…”
mentioning
confidence: 99%
“…34 When bovine antibodies are used for prophylaxis, similar or lower doses as compared to human antibodies would be expected to be effective provided that the cows are specifically immunized. In challenge studies performed by Tacket and coworkers, 35 complete protection against E. coli challenge in adult volunteers was seen using a daily oral administration of 5 g of bovine immunoglobulin from hyperimmunized animals. In a piglet model of human rotavirus infection, 0.6-1 g per day also sufficed to afford protection.…”
Section: Discussionmentioning
confidence: 99%